HUBUNGAN SELF EMPOWERMENT DENGAN KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 - Rahmat Tulloh Amin (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Diabetes Mellitus (DM) type 2 is a disease caused by increased levels of glucose in the blood (hyperglycemia) caused by abnormalities in insulin and insulin action. One of the factors that cause high blood glucose levels is poor self-empowerment. Effective efforts to prevent and control diabetes must face factors accompanied by regular and continuous monitoring through increasing self-empowerment, namely the ability of individuals to have control over their own choices regarding health. The purpose of this study was to determine the relationship between self-employment and blood glucose levels in patients with type 2 diabetes. This research method was cross-sectional with a sample of 50 patients with diabetes mellitus who were taken using simple random sampling technique. The measuring instrument used in the self-empowerment variable is the Diabetes Empowerment Scale (DES). and for blood glucose variables using a calibrated e-touch measuring instrument. Then the data were analyzed using the chi-square test. The results of the analysis in the category of self-empowerment in DM patients were at the 68% level and blood glucose levels were in the high category 70%. Then the results of the bivariate analysis showed a p-value of 0.00 < (0.05) so that it could be concluded that there was a relationship between self-empowerment and self-empowerment. empowerment with blood glucose levels in DM patients. Self-empowerment strategies were developed in DM patients to improve their control of their disease, especially glucose levels by increasing physical activity, improving healthy eating patterns and promoting better and more prosperous mental health. Keywords: Diabetes Mellitus, Glucose Level, Self Empowerment